A Novel SIW H-Plane Horn Antenna Based on Parabolic Reflector - Shiqiao Zhang; Zheng Li; Junhong Wang (International Journal of Antennas and Propagation)
A new type of H-plane horn antenna based on the parabolic reflector principle is proposed in this paper. The parabolic reflector is constructed with the substrate integrated waveguide technology and is used for generating large radiation aperture and uniform phase distribution at the aperture, yielding a fan beam with very narrow beamwidth in H-plane. A feeding source composed of a probe and an inductive-post reflector is designed as the feed, which can transmit a unidirectional incident wave toward the parabolic reflector. Two metallic strips with post arrays are designed as a transition for the matching between the horn aperture and the free space and also work as a director to realize unidirectional radiation and reduce the front-to-back ratio. The antenna has the advantages of narrow beam, compact size, and easy integration, and the operation bandwidth is from 27 GHz to 35.5 GHz. The experimental results show good agreement with the simulated results.